2017
DOI: 10.1152/ajprenal.00194.2017
|View full text |Cite
|
Sign up to set email alerts
|

PGE2upregulates renin through E-prostanoid receptor 1 via PKC/cAMP/CREB pathway in M-1 cells

Abstract: During the early phase of ANG II-dependent hypertension, tubular PGE is increased. Renin synthesis and secretion in the collecting duct (CD) are upregulated by ANG II, contributing to further intratubular ANG II formation. However, what happens first and whether the triggering mechanism is independent of tubular ANG II remain unknown. PGE stimulates renin synthesis in juxtaglomerular cells via E-prostanoid (EP) receptors through the cAMP/cAMP-responsive element-binding (CREB) pathway. EP receptors are also exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 46 publications
(67 reference statements)
4
30
0
Order By: Relevance
“…Another key finding of the current study was that PGE2 activated the CREB/BDNF/TrkB signaling pathway, which induced KLF4 expression and then stimulated the polarization of macrophage M2 in DMAS mice. In a prior study, PGE2 was found to increase the level of cAMP and the extent of CREB phosphorylation 29 . Similarly, another study also confirms that BDNF expression and the extent of CREB phosphorylation are increased by treatment with the PGE2 analog, 16,16 dimethyl PGE2 (dmPGE2), in dorsal root ganglion explant cultures 30 .…”
Section: Discussionmentioning
confidence: 64%
“…Another key finding of the current study was that PGE2 activated the CREB/BDNF/TrkB signaling pathway, which induced KLF4 expression and then stimulated the polarization of macrophage M2 in DMAS mice. In a prior study, PGE2 was found to increase the level of cAMP and the extent of CREB phosphorylation 29 . Similarly, another study also confirms that BDNF expression and the extent of CREB phosphorylation are increased by treatment with the PGE2 analog, 16,16 dimethyl PGE2 (dmPGE2), in dorsal root ganglion explant cultures 30 .…”
Section: Discussionmentioning
confidence: 64%
“…cAMP is the major second messenger involved in the control of renin production [ 9 , 11 , 38 ]. In this study, we observed that the activation of the cAMP pathway in As4.1 cells with adenyl cyclase activator forskolin resulted in a time-dependent elevation in renin protein level at the MW of 50 kDa ( Figure 4 A).…”
Section: Resultsmentioning
confidence: 99%
“…The accumulated cAMP activates PKA, which phosphorylates several proteins and regulates a wide spectrum of cell behaviors. It has been reported that elevated cAMP stimulates renin gene expression in JG cells by phosphorylation of CREB through PKA [ 9 , 11 ]. Consistent with these reports, the elevation in renin in this study was preceded by CREB phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although, cAMP/PKA is the main signaling pathway involved in CREB phosphorylation, PKC can also phosphorylate CREB (Brindle and Montminy, 1992). However, we demonstrated that in the CD, the PKC pathway plays a major effect on the activation of renin synthesis (Gonzalez et al, 2015(Gonzalez et al, , 2017Lara et al, 2017).…”
Section: Discussionmentioning
confidence: 69%